Turning Show’n’Tell into Democratic Dialogue - Andrea Davy; Willow Brown (Networks: An Online Journal for Teacher Research, 2006)
In this paper, I summarize an intense two-week study that I participated in at a Summer Institute on Education and Democracy at the University of Manitoba, Canada, beginning with brief descriptions of the innovation, Nos histoires, the purpose of the study, and the research method. I share the action research process and my reflections using Brown’s (2004) meaning-making model of action research, the learning circle, as an organizing framework. The four stages of this model, Wholeness, Awareness, Meaning, and Commitment, are used as headings to report stages of the study. This framework helped me align a series of actions with an overall purpose, and integrate objective knowledge from several lines of research with my own classroom experience and beliefs. The learning circle also helped me gain reflective skills for framing other educational problems and designing creative solutions. A careful description of the way my work was guided by this framework may help other teachers adapt the process for themselves.